Awareness and expectations of visitors to family medicine practices about palliative care in Slovenia: Osveščenost in pričakovanja obiskovalcev ambulant družinske medicine o paliativni oskrbi v Sloveniji - Zelko, Erika; Gašpar, Dorotea; Gjuras, Estera; Krčevski Škvarč, Nevenka (Acta Medico-Biotechnica, 2022)
Purpose: In Slovenia, palliative medicine and care are developing more intensively in the last years. Appraisal of the existing evidence on, expectations in, and awareness about palliative care (PC) in Slovenia is essential to inform the emerging practice and future research.Methods: A cross–sectional survey of 2000 individuals aged over 18 years old was performed. Information was collected using a structured questionnaireconsisting of 18 items. Analysis of the questions is presented using descriptive statistics. The significance level was set at p ≤0.05 in all analyses.Results: 58.6% of participants report having little awareness of PC, with most information received via media (radio, TV, internet) and experience obtaineddirectly or through family and friends. In this sample, increasing age, being female and higher levels of education were related to higher reported levels of awareness of PC. 69.6% of our participants said they wish to die at home. According to our participants, patients at home need, their physical symptoms be well controlled (93.8%), followed by medical and health care (65.9%), and support from voluntary carers (41.4%) and they also highlighted the wish of relatives and patients to be consulted via telephone by a health care providers in case of problems (55.4%). 28.4% confirmed they know the advance healthcare directive form.Conclusion: The survey data presented here provides an empirical basis from which we can begin stimulating discussions about death, dying and support empowered decision–making, as confronting end of life issues is inevitable for us all. All patients have the right to dignity and peace through their last stages of life.